Influential Cognitive Processes on Framing Biases in Aging - Perez, Alison M.; Spence, Jeffrey Scott; Kiel, L. D.; Venza, Erin E.; Chapman, Sandra B. (Frontiers in Psychology, 2018)
Factors that contribute to overcoming decision-making biases in later life pose an important investigational question given the increasing older adult population. Limited empirical evidence exists and the literature remains equivocal of whether increasing age is associated with elevated susceptibility to decision-making biases such as framing effects. Research into the individual differences contributing to decision-making ability may offer better understanding of the influence of age in decision-making ability. Changes in cognition underlying decision-making have been shown with increased age and may contribute to individual variability in decision-making abilities. This study had three aims; 1) to understand the influence of age on susceptibility to decision-making biases as measured by framing effects across a large, continuous age range; 2) to examine influence of cognitive abilities that change with age; and 3) to understand the influence of individual factors such as gender and education on susceptibility to framing effects. 200 individuals (28-79 years of age) were tested on a large battery of cognitive measures in the domains of executive function, memory and complex attention. Findings from this study demonstrated that cognitive abilities such as strategic control and delayed memory better predicted susceptibility to framing biases than age. The current findings demonstrate that age may not be as influential a factor in decision-making as cognitive ability and cognitive reserve. These findings motivate future studies to better characterize cognitive ability to determine decision-making susceptibilities in aging populations.